Pembelajaran Inkuiri Terbimbing Melalui Kegiatan Lab Virtual dan Eksperimen Riil untuk Peningkatan Penguasaan Konsep dan Pengembangan Aktivitas Siswa (UPEJ Unnes Physics Education Journal, 2018)
This study aims to describe students’ activities and to determine more effective treatment for improving the concepts achievement between the guided inquiry through real experimental activity or virtual lab activity. This study was a pre-experiment with one group pretest-posttest type. Sampling technique using a purposive sampling. Class experiment 1 was taught by guided inquiry learning through real experiment activities and class experiment 2 was taught by guided inquiry learning through virtual lab activities. Data were collected using test and observation method. The value of experiment class 1 (3,71)> of class experiment 2 (2,10), it means that guided inquiry learning through real experiment activity more effective to improve the concepts achievement of students than virtual lab activity. The gain test of the students' activity development of experiment class 1 was 0,37 (medium) and experiment class 2 was 0,31 (medium), it means that real experiment and virtual lab activities were effective to develop students’ activities.